Nutrient management for quality seed production in amaranth (Amaranthus tricolor) - Sheeba Rebecca Isaac, (Seed Research, 2026)
A field experiment was conducted in Kollam district, southern Kerala during 2009- 2010 to study the influence of different nutrient sources on the seed production in red Amaranth (Amaranthus tricolor) variety Arun. The NPK dose of 112.5:50:62.5 kg ha¹ was given in 12 combinations of different sources of nutrients. The results revealed that significant higher seed yields of 607.89 kg ha and 517.17 kg ha¹ were recorded in the treatments in which the nutrient and were supplied through organic sources at 100 and 150 percent of recommended dose. Seed quality traits such as 1000 seed weight and vigour index were also significantly higher in organically grown seed crop. Higher B:C ratio was observed in inorganic treatments, despite lower yields as compared to organic treatments. This can be attributed to the lower cost of nutrient inputs, compared to the bulk quantity of organic sources required for the varying levels of substitution.